2014
DOI: 10.1080/10402381.2013.876132
|View full text |Cite
|
Sign up to set email alerts
|

Experimental additions of aluminum sulfate and ammonium nitrate toin situmesocosms to reduce cyanobacterial biovolume and microcystin concentration

Abstract: Experimental additions of aluminum sulfate and ammonium nitrate to insitu mesocosms to reduce cyanobacterial biovolume and microcystin concentration, Lake and Reservoir Management, 30:1, 84-93,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Orihel and others (2012) reported that high microcystin concentrations were detected only at low total nitrogen (TN) to total phosphorus (TP) ratios (TN:TP) in a study of Canadian lakes from 2001 to 2011. To further understand this concept, large scale mesocosm experiments were led by Harris and others (2014a;2014b). The experiments were completed in an Oregon reservoir where TN:TP ratios were manipulated by adding ammonium nitrate and aluminum sulfate, where the manipulation of the TN:TP greater than 50 (by mass) shifted the dominant primary producers from cyanobacteria to the more ecologically desirable chlorophytes and cryptophytes.…”
Section: Detection Of Microcystin and Other Cyanotoxins In Lakes Normentioning
confidence: 99%
“…Orihel and others (2012) reported that high microcystin concentrations were detected only at low total nitrogen (TN) to total phosphorus (TP) ratios (TN:TP) in a study of Canadian lakes from 2001 to 2011. To further understand this concept, large scale mesocosm experiments were led by Harris and others (2014a;2014b). The experiments were completed in an Oregon reservoir where TN:TP ratios were manipulated by adding ammonium nitrate and aluminum sulfate, where the manipulation of the TN:TP greater than 50 (by mass) shifted the dominant primary producers from cyanobacteria to the more ecologically desirable chlorophytes and cryptophytes.…”
Section: Detection Of Microcystin and Other Cyanotoxins In Lakes Normentioning
confidence: 99%
“…Currently, the magnitude and toxicity of cHABs in Lake Erie and other Great Lakes now present significant risks to drinking water supplies, beaches, fisheries, and other sectors (Carmichael, 2013). More recent studies have linked N:P ratios with an increased risk of toxin (microcystin, MC)-producing cHABs (Orihel et al, 2012;Harris et al, 2014). Blooms dominated by N 2 -fixing cyanobacteria have been linked to the availability of N relative to P (or N:P ratio), although this relationship is widely debated (Smith et al, 1999;Elser et al, 2007;Downing et al, 2001;Conley et al, 2009;Schindler, 2012).…”
Section: A Nutrientsmentioning
confidence: 99%
“…Some studies have applied barley straw or its extract to reduce cyanobacterial and other algal blooms in small waterbodies (Xiao et al, 2010). Chemical treatment with aluminum sulfate (alum; Steinman et al, 2004;Harris et al, 2014), liming (Prepas et al, 2001), or lanthanum-infused bentonite clay (Robb et al, 2003) is designed to precipitate water column nutrients and form a thin layer on the sediment surface to reduce sediment loading. In some cases the cell-bound nutrients that are released by this treatment may actually stimulate cyanobacterial growth (Xiao et al, 2010).…”
Section: Chab Managementmentioning
confidence: 99%
See 1 more Smart Citation